2021
DOI: 10.1111/apps.12358
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive fatigue in young, middle‐aged, and older: Breaks as a way to recover

Abstract: Maintaining productivity is of primary importance in organizational settings. Nowadays, the pressure for work efficacy is required until advanced age given the increased longevity in western societies. Worryingly,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…A study of first‐time hearing aid users found hearing aid fitting led to reduced listening fatigue but had no effect on general mental fatigue (Holman, Drummond, & Naylor, 2021), suggesting that hearing aids alone may not be sufficient to reduce fatigue. In healthy working‐age adults, interventions that incorporate micro‐breaks into demanding tasks (Gilsoul et al, 2021) or the working day (Radwan et al, 2022) have been shown to reduce the impact of cognitive demands on mental fatigue. Micro‐breaks have the potential to reduce mental fatigue for individuals with hearing loss and to facilitate greater capacity for participation in physical activities.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A study of first‐time hearing aid users found hearing aid fitting led to reduced listening fatigue but had no effect on general mental fatigue (Holman, Drummond, & Naylor, 2021), suggesting that hearing aids alone may not be sufficient to reduce fatigue. In healthy working‐age adults, interventions that incorporate micro‐breaks into demanding tasks (Gilsoul et al, 2021) or the working day (Radwan et al, 2022) have been shown to reduce the impact of cognitive demands on mental fatigue. Micro‐breaks have the potential to reduce mental fatigue for individuals with hearing loss and to facilitate greater capacity for participation in physical activities.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…All participants gave their informed consent to participate, and the study was approved by the Ethics Committee of the Faculty of Psychology and Educational Sciences of the University of Liège and was in accordance with the Declaration of Helsinki (1964). Participants included here were also used as control group in another study investigating the effects of breaks as a way to recover from fatigue (Gilsoul, Libertiaux & Collette, 2022).…”
Section: Participantsmentioning
confidence: 99%
“…Sustained cognitive fatigue leads to poor performance at work, causes workplace accidents, reduced test scores in students, etc. [3]. CF is one of the main reasons of day to day accidents too.…”
Section: Introductionmentioning
confidence: 99%